PENGARUH DESKRIPSI PEKERJAAN, PENGAWASAN DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI POLISIDI KEPOLISIAN RESOR LABUHANBATU - Solihuddin Hasibuan; Zainal Abidin; Aca Ciputri Cis; Zainan Nur; Nurmalan Harahap (Universitas Islam Islam Sumatera Utara, 2020)
This research aims to determine and analyze : 1) the effect of job descriptions on the commitment of the Police organization in Labuhanbatu District Police; 2) the effect of supervision on the commitment of the Police organization in Labuhanbatu District Police; 3) the influence of career development on the commitment of the Police organization in Labuhanbatu District Police; and 4) job description, supervision and career development towards the commitment of the Police organization in Labuhanbatu District Police. The sample in this research amounted to 75 people with sample monitoring techniques using the stratified random sampling method. The results showed : 1) the job description had a positive and significant effect on the commitment of the police organization in Labuhanbatu District Police; 2) supervision has a positive and significant impact on the commitment of police organizations in Labuhanbatu District Police; 3) career development has a positive and significant impact on the commitment of police organizations in Labuhanbatu District Police; 4) simultaneous job description, supervision and career development have a positive and significant effect on the commitment of the police organization in Labuhanbatu District Police. The commitment of police organizations can be influenced by job description, supervision and career development by 64.7%, while the remaining 35.3% organizational commitment is influenced by other factors outside the research variable.